2022
DOI: 10.3324/haematol.2022.281631
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of measurable residual disease status to prediction accuracy of relapse and survival in adults with acute myeloid leukemia undergoing allogeneic hematopoietic cell transplantation

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Although the retrospective nature does not allow to make direct comparisons between MAC and RIC populations due to baselines differences, MAC could not abrogate the adverse prognosis of MRD+ before HSCT, and the survival of MRD+ patients who received MAC was similar to RIC patients (both MRD− and MRD+). In line with our results, several studies demonstrate significant differences depending on the MRD status in patients receiving MAC, whereas this factor did not influence on OS and EFS on RIC patients ( 23 , 28 , 32 , 34 ). In the meta-analysis performed by Buckley et al., patients with MRD+ by different methods, including several studies using MFC, had significantly worse EFS an OS, and MAC was unable to attenuate the negative effects of a positive pretransplant MRD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the retrospective nature does not allow to make direct comparisons between MAC and RIC populations due to baselines differences, MAC could not abrogate the adverse prognosis of MRD+ before HSCT, and the survival of MRD+ patients who received MAC was similar to RIC patients (both MRD− and MRD+). In line with our results, several studies demonstrate significant differences depending on the MRD status in patients receiving MAC, whereas this factor did not influence on OS and EFS on RIC patients ( 23 , 28 , 32 , 34 ). In the meta-analysis performed by Buckley et al., patients with MRD+ by different methods, including several studies using MFC, had significantly worse EFS an OS, and MAC was unable to attenuate the negative effects of a positive pretransplant MRD.…”
Section: Discussionsupporting
confidence: 92%
“…Several other published studies also reported that MRD+ had an impact on EFS due to an increased CIR ( 5 , 17 , 21 , 22 ). Furthermore, in many others, MRD+ also had an impact on OS ( 8 , 13 , 23 34 ). Although the incidence of relapse was higher in MRD+ patients, that did not have a statistically significant impact on OS in our cohort, maybe due to the shortest follow-up in the MRD− group.…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with the performance characteristics of the assay and our approach in previous analyses, any level of MRD was considered MRD + . 12 , 13 , 14 , 15 …”
Section: Methodsmentioning
confidence: 99%
“…Arbolí et al [19] developed a neural network method for disease status classification of patients. The model outperformed SVM (Support Vector Machine), random forest, and decision tree models, successfully learning the high-dimensional EHR (Electronic Health Record) data structure of phenotype hierarchy.…”
Section: B Medical Document Classification Modelsmentioning
confidence: 99%